2019
DOI: 10.1002/kjm2.12009
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk and the association with accessibility coverage to medical facilities and socioeconomic status among heroin users in Kaohsiung, Taiwan (2011‐2015): A GIS approach

Abstract: Illegal drug use has caused considerable health and social costs. Access to medical treatment has been one of the most cost‐effective interventions to reduce problematic drug use. Accessibility to treatment, which can be analyzed by the spatial approach such as geographic information system (GIS), has thus been utilized as a measure of the proportion of population that reaches appropriate health services. In this study, the association of accessibility coverage to medical facilities and socioeconomic status wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For example, using enhanced 2-step floating catchment area method, Wan et al (2012) found that spatial access to oncologists is negatively relate to the colorectal cancer survival in rural Texas while not in urban settings. Feng et al (2019) found that the HIV incidences among the heroin users can be effectively reduced if they are within the 1.5 km coverage of medical facilities in Kaohsiung (Gaoxiong). A study conducted in eastern France indicated that low spatial access to urban physical activity facilities and to general food outlet could lead to a higher likelihood of being overweight for blue-collar worker's children (Casey et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, using enhanced 2-step floating catchment area method, Wan et al (2012) found that spatial access to oncologists is negatively relate to the colorectal cancer survival in rural Texas while not in urban settings. Feng et al (2019) found that the HIV incidences among the heroin users can be effectively reduced if they are within the 1.5 km coverage of medical facilities in Kaohsiung (Gaoxiong). A study conducted in eastern France indicated that low spatial access to urban physical activity facilities and to general food outlet could lead to a higher likelihood of being overweight for blue-collar worker's children (Casey et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%